SAT0227 The Efficacy of Vasoactive and Vasodilating Drugs on Digital Ulcers Healing in Systemic Sclerosis: Data from The Desscipher Observational Study of Eustar Group. (15th July 2016) - Abignano, G.; Blagojevic, J.; Allanore, Y.; Avouac, J.; Cometi, L.; Czirják, L.; Denton, C.; Distler, O.; Frerix, M.; Guiducci, S.; Huscher, D.; Jaeger, V.K.; et al.
Abstract : Background: Digital ulcers (DU) are an important driver of poor quality of life in Systemic Sclerosis (SSc). Real life clinical management of DU includes the use of vasoactive (Bosentan) and vasodilating (Sildenafil, Iloprost, CCB and ACE inhibitors) drugs in different combinations, without strong evidence for efficacy. Objectives: One of the aims of the EC-funded FP7 research project DeSScipher (acronym for "to decipher the optimal management of SSc") was to determine the relative effectiveness of the above treatments for the healing of DU in SSc patients. Methods: Twenty eight centres in Europe participated to the study. Longitudinal data were collected over 24 months in a specific web based EUSTAR database. The DU distal to PIP joints at the inclusion visit or developed over the follow-up were included. End-points included: mean number of healed ulcers/patient; proportion of patients with healed DU; and time to healing of at least one DU. Results: Out of 1394 enrolled patients, 265 met inclusion criteria. Follow-up data were available for 156 patients. 57% of patients were on vasodilators (Sildenafil, Iloprost, CCB, alone or in combination), 5.8% were on single vasoactive drug (Bosentan) and 37.2% patients were on combination therapy. The mean number of DU/patient at the inclusion visit was comparable among the 3 treatment arms. At 12 and 24 months, the mean number of healed DU/patient was higher in the vasodilator group compared to the vasoactive and combination groups (1.8 vs 1 vs 1.2, p=0.013 and 2.4 vs 1.3 vs 1.3, p=0.018 respectively). No significant difference was observed at 6 months. The proportion of patients with all or at least one DU healed was not significantly different between treatment arms. Initial exploratory analysis also suggested that the estimated mean time to healing of at least one DU was 9.71±2.2 months in vasoactive arm, 8.7±0.5 in vasodilator arm and 7.9±0.6 in combination therapy arm. Further, when considered separately, patients on Sildenafil (±CCB) showed the highest healing rate at 6months follow-up, compared to other drug combinations. However, correction for concurrent treatment and confounding factors is still on going. Conclusions: Vasodilating treatment achieved a major number of healed DU at 12 and 24 months. The combination treatment seems to be of help in obtaining a shorter time to healing and limiting observation at 6 months may bias overall interpretation of data. Further analysis is ongoing for different drug combination at different time-points. Acknowledgement: The DeSScipher project was funded by the European Community's Framework Programme 7 (FP7-HEALTH-2012.2.4.4–2 - Observational trials in rare diseases) under grant agreement N° 305495. Disclosure of Interest: None declared